EFEKTIFITAS KONSELING ANALISIS TRANSAKSIONAL TENTANG DIET CAIRAN TERHADAP PENURUNAN INTERDIALYTIC WEIGHT GAIN (IDWG) PASIEN GAGAL GINJAL KRONIS YANG MENJALANI HEMODIALISA DI RUMAH SAKIT UMUM DAERAH KARDINAH - Sri Hidayati; Ratna Sitorus; Masfuri - (Universitas Muhammadiyah Semarang, 2014)
Transactional Analysis Counseling is a form of counseling that can be applied to overcome theincreases of Interdialytic Weight Gain in patients with chronic renal failure. The goal of thisresearch was to determine the effectiveness of transactional analysis counseling on a liquid diettowards the reduction of Interdialytic Weight Gain in patients with chronic renal Failure whowere undergoing hemodialysis. This study used a quasi experiment design approach to pretestposttest control group design. The respondents of this study were 24 patients. Univariate andbivariate analyzes were using the statistical of test t-test and ANNOVA. The conclusion of thisresearch showed that the transactional analysis counseling effects the reduction of Interdialytic Weight Gain with p = 0.0003. Therefore, nurses are advised to apply transactional analysiscounseling to anticipate the enhancement of Interdialytic Weight Gain.Keywords : Nurse, Transactional Analysis, Chronic renal failure, hemodialysis, InterdialyticWeight Gain